Modeling and optimization of an integrated multi-generation solar system with variable heat to power ratio for supplying residential and industrial demands - Hajialigol, Parisa; Fathi, Amirhossein; Saboohi, Yadollah (Renewable energy, 2021)
The paper aims to present a supply model to satisfy the required household final energy carriers, freshwater and industrial cooling loads for a deprived area of access that is located in hot and humid climate. To this aim, a multi-generation hybrid solar thermophotovoltaic integrated system with capability of adjusting heat to power ratio dynamically is introduced. Appropriate analytical tools are developed to obtain the optimal capacity of any systems and energy flows subject to the technology and demand constraints, the financial limitation and the constraints defined by the politicians and local government. The demand constraints are identified through the field studies and the comfort conditions. Moreover, the required final energy carriers are quantified by using an engineering software that observe the interaction among the useful energy demands due to the conversion technologies. The large optimization problem caused by the dynamic of the system is reduced through merging the constraints. The constraint coefficient matrix reduced by 91% in the case study with negligible effect on the accuracy. The results show the multi-generation system contribution to meet the local demand is 35%. However, the electricity generated is 83 times higher than the local demand, the difference is sold to the national network. •A supply model is designed based on TPV coupled with a thermal cycle and CPC.•The system is to satisify final energy and fresh water demands.•The system configuration provides opportunity to adjust the heat to power ratio.•A creative approach is presented to lower the computational load.